Profiling the Physiological Roles in Fish Primary Cell Culture - Lingjie He; Cheng Zhao; Qi Xiao; Ju Zhao; Haifeng Liu; Jun Jiang; Quanquan Cao (Biology, 2023)
Fish primary cell culture has emerged as a valuable tool for investigating the physiological roles and responses of various cell types found in fish species. This review aims to provide an overview of the advancements and applications of fish primary cell culture techniques, focusing on the profiling of physiological roles exhibited by fish cells in vitro. Fish primary cell culture involves the isolation and cultivation of cells directly derived from fish tissues, maintaining their functional characteristics and enabling researchers to study their behavior and responses under controlled conditions. Over the years, significant progress has been made in optimizing the culture conditions, establishing standardized protocols, and improving the characterization techniques for fish primary cell cultures. The review highlights the diverse cell types that have been successfully cultured from different fish species, including gonad cells, pituitary cells, muscle cells, hepatocytes, kidney and immune cells, adipocyte cells and myeloid cells, brain cells, primary fin cells, gill cells, and other cells. Each cell type exhibits distinct physiological functions, contributing to vital processes such as metabolism, tissue regeneration, immune response, and toxin metabolism. Furthermore, this paper explores the pivotal role of fish primary cell culture in elucidating the mechanisms underlying various physiological processes. Researchers have utilized fish primary cell cultures to study the effects of environmental factors, toxins, pathogens, and pharmaceutical compounds on cellular functions, providing valuable insights into fish health, disease pathogenesis, and drug development. The paper also discusses the application of fish primary cell cultures in aquaculture research, particularly in investigating fish growth, nutrition, reproduction, and stress responses. By mimicking the in vivo conditions in vitro, primary cell culture has proven instrumental in identifying key factors influencing fish health and performance, thereby contributing to the development of sustainable aquaculture practices.